Exploration of the Teaching Factory Program at Vocational Schools Majoring in Laboratory Testing Analysis in East Java - Chorera, Aprilia; Dasna, I Wayan; Joharmawan, Ridwan (Universitas Negeri Malang, 2024)
Due to the imbalance in national education goals for vocational school students in the Teaching Factory program, the research aims to explore the application, obstacles faced, and the role of DUDI (business and industrial) in the Teaching Factory program in schools. This research was carried out at five State Vocational Schools majoring in laboratory testing analysis in East Java. This research uses qualitative research with an ethnographic design. Data collection techniques include in-depth interviews, observation, and documentation. The subjects of this research were 20 people: the headmasters, deputy principal for curriculum, head of the Laboratory Test Analysis skills program, Productive Teachers, Industry, and 3 students each. Data validity techniques use prologue engagement, participant observation, and triangulation. Data analysis is done through data reduction, data presentation, conclusion, and verification. The research results obtained (1) teaching factory activities at State Vocational Schools majoring in Laboratory Testing Analysis in collaboration with DUDI, which works in the Analysis field. This collaboration is related to student competencies that students need when they work in the factories (2) Practices in the Teaching Factory program are carried out in the TeFa (Teaching Factory) Laboratory, which has been specially prepared for this program, the preparation of the program and TeFa product results have been adjusted to DUDI (business and industrial standard) work. The research results provide recommendations for improving the teaching factory program in vocational schools to align the linear learning curriculum with DUDI.